Computed tomography-guided percutaneous microwave ablation of hepatocellular carcinoma in challenging locations: safety and efficacy of high-power microwave platforms. (18th August 2018) - Filippiadis, Dimitrios K.; Spiliopoulos, Stavros; Konstantos, Chrysostomos; Reppas, Lazaros; Kelekis, Alexis; Brountzos, Elias; Kelekis, Nikolaos
Abstract: Objective: To evaluate the clinical efficacy/safety of CT-guided percutaneous microwave ablation for HCC in challenging locations using high-power microwave platforms. Materials and methods: A retrospective review was conducted in 26 patients with 36 HCC tumours in challenging locations (hepatic dome, subcapsular, close to the heart/diaphragm/hepatic hilum, exophytic) undergoing CT-guided percutaneous microwave ablation in a single centre since January 2011. Two different microwave platforms were used both operating at 2.45 GHz: AMICA and Acculis MWA System. Patient demographics including age, sex, tumour size and location, as well as technical details were recorded. Technical success, treatment response, patients survival and complication rate were evaluated. Results: Treated tumours were located in the hepatic dome ( n  = 14), subcapsularly ( n  = 16), in proximity to the heart ( n  = 2) or liver hilum ( n  = 2), while two were exophytic tumours at segment VI ( n  = 2). Mean tumour diameter was 3.30 cm (range 1.4–5 cm). In 3/26 patients (diameter >4 cm), an additional session of DEB-TACE was performed due to tumour size. Technical success rate was 100%; complete response rate was recorded in 33/36 tumours (91.6%). According to Kaplan–Meier analysis, survival rate was 92.3% and 72.11% at 24- and 60-month follow-up, respectively. There were no major complications; two cases of minor pneumothorax and two cases of small subcapsular haematoma were resolved only with observation requiring no further treatment. Conclusion: CT-guided percutaneous microwave ablation for hepatocellular carcinoma tumours in challenging locations and up to 5 cm in diameter can be performed with high efficacy and safety rates.